THE CORRELATION BETWEEN PRONUNCIATION ANXIETY AND MOTIVATION - Amedea Cathriona Maharia; Noor Rachmawaty; Susilo Susilo (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
This study reports on quantitative study, conducted among 48 English majors, examining the relationship between a language-skill-specific type of anxiety—pronunciation anxiety and motivation. Pronunciation anxiety is presented as a feeling of apprehension and worry deriving from negative self-perceptions, and beliefs. The fears related specifically to pronunciation (Baran–Lucarz, 2014). When motivation is concerned, it has been conceptualized on the basis of the L2 Motivational Self System Model (Dörnyei, 2005), as the desire to reach highest communication proficiency levels nativelike target language accent, represented by the ideal L2 self and ought-to L2 self. The result of the calculation to find the correlation between pronunciation anxiety and motivation were having correlation but not significant. The data from 2 questionnaires which were calculated by using Pearson product moment formula showed most of subcomponents of PMQ and MPA had correlation but not significant, only between pronunciation anxieties to talk outside the classroom with Criterion Measure which had correlation and they were significant. The results showed in the table that Pearson correlation between PA-cl and Criter.Meas were -777*, it meant if the pronunciation anxiety to talk to native and non-native speaker outside the Fl-classroom was high than the strength of desire to achieve target language native-like pronunciation free from L1 influenced would be low. There was correlation but not significant between the level of motivation to reach a target language, represented by the Ideal L2 Self and the Ought to L2 Self of high and low PA students. However, in the level of motivation between high and low PA students to become communicative in the Tl, represented the Ideal L2 Self and Ought to L2 self was found significantly difference.